Football training specificity - Training individualization within the collective periodization - Baptista, I. (The Arctic University of Norwa, 2019)
Within the literature, different playing positions present different external load profiles in match-play and are associated with the individual variation in activity profiles. In contrast to detailed information regarding matches, few studies have focused on the training practices in football. Therefore, the aim of this thesis is to assess the levels of specificity that different playing-positions are subject to during trainings in an elite football club. Paper 1 highlights some challenges encountered when using positional data as part of research. This paper includes two studies where different tracking systems were compared during training practices. Papers 2 and 3 present the physical demands of official matches across playing positions and analyse how different tactical systems affect the players physical performance. In these papers (and in Paper 5) we used the ZXY Sport Tracking system to collect physical performance data from professional football players from an elite club in trainings and matches. Most existing technology in football relies on post-game/training analysis, however, its weakness is the lack of instant feedback during matches and trainings. Therefore, in Paper 4 we developed Metrix: a computerized toolkit for coaches to perform real-time monitoring and analysis of the players` performance. In Paper 5 we quantified and compared: a) the most demanding passages of play in trainings and matches; b) and the accumulated load of typical microcycles and official matches, per playing position. Match demands were overperformed for accelerations (131-166%) and decelerations (108-134%), by all the playing positions. However, relative to match values, training values for sprinting distance and high-intensity running distance were considerably lower (36-61% and 57-71%) than for accelerations and decelerations. In fact, some physical performance variables seem to be neglected in trainings, and to prepare players of different playing positions to successfully perform their match demands, a higher level of training specificity is required. Has part(s) Paper 1: Pettersen, S.A., Johansen, H.D., Baptista, I.A.M., Halvorsen, P. & Johansen, D. (2018). Quantified Soccer Using Positional Data: A Case Study. Frontiers in Physiology, 9:866. Also available in Munin at https://hdl.handle.net/10037/13999.